Size, value and liquidity: Do they really matter on an emerging stock market? - Judith Lischewski; Svitlana Voronkova (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The paper extends the evidence on the factors relevant for pricing stocks in emerging markets. While previous literature focused on Latin American and Asian developing markets, Central and Eastern European markets remain under-researched. By focusing on the Polish stock market, we aim to fill in a gap in the asset pricing literature and draw attention to these previously overlooked markets. In addition to analyzing the importance of the most prominent risk-factors such as market, size and book-to-market value, we investigate whether liquidity plays a role in pricing Polish stocks. To test this conjecture we use the largest array of liquidity measures that has been used in the literature to date. We take advantage of a hand-collected dataset covering the longest period studied so far in case of the this market. Our results support existing evidence for developed markets with regard to the market, size, and book-to-market factor. However, in contrast to studies on other emerging markets, we do not find convincing evidence in favour of the liquidity risk premium on the Polish stock market. This result is robust across various liquidity measures and time periods. Analyzing specific characteristics of the Polish market, we consider possible explanations behind this finding.
Keywords: G10; G12; 330; Aktienmarkt; Aufstrebende Märkte; Marktliquidität; Kapitalertrag; Bid-Ask Spread; Schätzung; Polen